Flux Growth and Superconducting Properties of (Ce,Pr)OBiS2 Single Crystals - Nagao, Masanori; Miura, Akira; Urushihara, Daisuke; Maruyama, Yuki; Goto, Yosuke; Mizuguchi, Yoshikazu; Moriyoshi, Chikako; Kuroiwa, Yoshihiro; Wang, Yongming; Watauchi, Satoshi; Asaka, Toru; Takano, Yoshihiko; et al. (Frontiers in Chemistry, 2020)
Ce1-xPrxOBiS2 (0.1 ≤ x ≤ 0.9) single crystals were grown using a CsCl flux method. Their structural and physical properties were examined by X-ray diffraction, X-ray absorption, transmission electron microscopy, and electrical resistivity. All of the Ce1-xPrxOBiS2 single crystals with 0.1 ≤ x ≤ 0.9 exhibited tetragonal phase. With increasing Pr content, the a-axis and c-axis lattice parameters decreased and increased, respectively. Transmission electron microscope analysis of Ce0.1Pr0.9OBiS2 (x = 0.9) single crystal showed no stacking faults. Atomic-resolution energy dispersive X-ray spectrometry mapping revealed that Bi, Ce/Pr, O, and S occupied different crystallographic sites, while Ce and Pr randomly occupied the same sites. X-ray absorption spectra showed that an increase of the Pr ratio increased the ratio of Cr4+/Ce3+. All of the Ce1-xPrxOBiS2 crystals showed superconducting transition, with a maximum transition temperature of approximately 4 K at x = 0.9.